Pengaruh Current Ratio (Cr) Dan Debt To Asset Ratio (Dar) Terhadap Kinerja Keuangan Perusahaan (Studi Kasus Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar di Bursa Efek Indonesia Pada Periode 2017-2022) - Putriadi, Regita Azkia; Harahap, Muhammad Nasim (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to examine the effect of Current Ratio (CR) and Debt to Asset Ratio (DAR) on financial performance proxied by Return on Asset (ROA) in food and beverage subsector companies listed on the Indonesia Stock Exchange in the 2017-2022 period. Financial performance is carried out to measure the performance of an organization within a certain period of time, which reflects the level of success in carrying out its activities. The number of samples used was 11 food and beverage sub-sector companies listed on the IDX for 2017-2022 and were obtained using a purposive sampling method. While the data used is in the form of secondary data with quantitative data types during the 2017-2022 period. This research method is descriptive statistics with the approach, namely the classical assumption test, and multiple linear analysis. Data is processed with the help of SPSS 25 software. Based on the results of the research carried out simultaneously with statistical tests showing that the Current Ratio and Debt to Asset Ratio variables simultaneously affect financial performance. The results of the partial Current Ratio research show that the results do not have a significant effect on financial performance.